Behaviour analysis in smart spaces - Oliveira, Pedro Filipe (2018)
We are on a new era of interaction between persons and physical spaces. Users want that those spaces smartly adapt to their preferences in a transparent way. This paper describes the process of planning, reasoning and modeling of a Smart Environment with domestic and industrial application, taking advantage of emerging wearable devices on the market (smart watches, fitness trackers, etc.) and newer wireless communication technologies (NFC, BLE, Wi-Fi Direct). Enabling in a noninvasive way for the user, optimize the efficiency, comfort, and safety at the environments. This approach can be applied in home automation, public spaces and also incorporated at industrial level, to help build smart and autonomous factories.